THE INFLUENCE OF E-SERVICE QUALITY AND ELECTRONIC WORD OF MOUTH (E-WOM) ON CUSTOMER SATISFACTION IN USING THE BRKS MOBILE APPLICATION IN PEKANBARU - Aprila, Nuraziza; Jamilah, Putri; Busyro, Wahyi; Septianingsih, Rika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Advances in information technology have driven significant transformation in the banking industry, including in the provision of Sharia-based mobile banking services. This study aims to empirically analyze the effect of e-service quality and electronic word of mouth (E-WOM) on the satisfaction of BRKS Mobile app users in Pekanbaru. This study uses a quantitative approach with a survey method and involves 100 respondents selected through purposive sampling. The research instruments were validated through validity and reliability tests, while hypothesis testing was conducted using multiple linear regression through SPSS software version 27. The results show that both variables have a positive and significant effect on customer satisfaction, both partially and simultaneously. The R² value of 0.255 indicates that 25.5% of customer satisfaction variation is explained by these two variables. These findings emphasize the importance of digital service quality and electronic word of mouth in enhancing user experience, and provide strategic implications for the development of technology-based Islamic banking services and social trust.